A novel complex of nucleoporins, which Includes Sec13p and a Sec13p homolog, is essential for normal nuclear pores - Siniossoglou, Symeon; Wimmer, Christian; Rieger, Michael; Doye, Valerie; Tekotte, Hildegard; Weise, Chris; Emig, Sonja; Segref, Alexandra; Hurt, Ed (Cell, 1996)
In a genetic screen for nucleoporin-interacting components, a novel nuclear pore protein Nup84p, which exhibits homology to mammalian Nup107p, was isolated. Nup84p forms a complex with five proteins, of which Nup120p, Nup85p, Sec13p, and a Sec13p homolog were identified. Upon isolation of Sec13p-ProtA, nucleoporins were still associated, but the major copurifying band was a 150 kDa protein, showing that Sec13p occurs in two complexes. Disruption of any of the genes encoding Nup84p, Nup85p, or Nup120p caused defects in nuclear membrane and nuclear pore complex organization, as well as in poly(A)+ RNA transport. Thus, the Nup84p complex in conjunction with Sec13-type proteins is required for correct nuclear pore biogenesis.
Elektronische Reproduktion der Druck-Ausgabe 27. Juli 2004
Gesehen am 02.12.2025